Factors influencing smallholder farmers’ participation in collective marketing: micro-level evidence from Ehlanzeni, South Africa - Magakwe, Nkhubedu Adelaide; Olorunfemi, Oluwasogo; Sithole, Ally (Frontiers in Sustainable Food Systems, 2025)
Engaging in markets is a critical step for smallholder farmers seeking to alleviate poverty, sustain their livelihoods, and contribute to local economic development. Collective market efforts is one of the promising pathways for transitioning smallholder farmers from no-profit market participants to successful market participants. Hence, this study was conducted to determine the market participation profile of smallholder farmers, examine their perception towards collective marketing, investigate the socio-economic factors influencing participation, and determine the constraints hindering engagements in collective market efforts among smallholder farmers in Ehlanzeni, South Africa. The researcher used a two-stage sampling procedure to sample a total of 300 smallholder farmers from Ehlanzeni district. Descriptive statistics, binary logistic and probit regression models were used to analyze the elicited data. The results showed that farming experience, farmer group membership, land ownership, frequency of extension officer visits, and selling diverse farm produce significantly influenced farmers’ participation in collective marketing. The results further indicate that constraints such as lack of proper storage facilities, lack of marketing information, and inability to cope with other farmers significantly influence participation in collective market initiatives. The study recommends improved and clear information sharing from advisory services on collective marketing and frequent functionality checks for smallholder farmers in collective action through proceedings of farmers’ day meetings and farmers’ market days, coupled with financial and postharvest storage facilities support, to scale up their participation for better income and livelihoods.